TRANSLATION AND VALIDATION OF THE BRAZILIAN PORTUGUESE VERSION OF THE GASTROINTESTINAL SYMPTOM RATING SCALE (GSRS) QUESTIONNAIRE - SOUZA,Gabriela Santos (2016)
ABSTRACT Background - Bowel function is a widely evaluated parameter in interventional and longitudinal studies since it is associated with good maintenance of health. The evaluation of intestinal function has been performed by many questionnaires, however, there are few options validated in Brazilian Portuguese. Objective - The aim of this work was to translate and validate into Brazilian Portuguese the Gastrointestinal Symptom Rating Scale (GSRS) questionnaire. Methods - Translation and cultural adaptation were performed according to a previously established methodology followed by reliability calculations. Results - The final translated GSRS questionnaire showed an adequate value of overall reliability of Cronbach's alpha of 0.83, and its domains were classified from acceptable to adequate. The overall test-retest reliability by intraclass correlation coefficient (ICC) was 0.84, considered excellent. Conclusion - The GSRS was translated and validated into Brazilian Portuguese, with appropriate internal consistency and reliability and is available to be used in assessments of bowel function.